2002
DOI: 10.1080/10715760290025933
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Trinitrotoluene-induced Reproductive Toxicity via Oxidative DNA Damage by its Metabolite

Abstract: Several epidemiological studies and animal experiments showed that 2,4,6-trinitrotoluene (TNT), a commonly used explosive, induced reproductive toxicity. To clarify whether the toxicity results from the interference of endocrine systems or direct damage to reproductive organs, we examined the effects of TNT on the male reproductive system in Fischer 344 rats. TNT administration induced germ cell degeneration, the disappearance of spermatozoa in seminiferous tubules, and a dramatic decrease in the sperm number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 55 publications
1
37
0
1
Order By: Relevance
“…An earlier study investigating TNT effects in WFL also demonstrated the slight increase, then a decrease, in testes mass over the range of TNT (McFarland et al 2008). The testes as a TNT target organ has been reported in other species and included atrophy with a decrease in mass (Dilley et al 1982;Levine et al 1990;Homma-Takeda et al 2002). When examining the stressors food and TNT (Table 2), the testes were the only organ that experienced a loss in mass due to both a decrease in food intake (p = 0.012) and TNT exposure (p \ 0.001), increasing the potential significance of this organ as a sensitive target organ for other environmental stressors.…”
Section: Effects On Organ Weightsmentioning
confidence: 86%
“…An earlier study investigating TNT effects in WFL also demonstrated the slight increase, then a decrease, in testes mass over the range of TNT (McFarland et al 2008). The testes as a TNT target organ has been reported in other species and included atrophy with a decrease in mass (Dilley et al 1982;Levine et al 1990;Homma-Takeda et al 2002). When examining the stressors food and TNT (Table 2), the testes were the only organ that experienced a loss in mass due to both a decrease in food intake (p = 0.012) and TNT exposure (p \ 0.001), increasing the potential significance of this organ as a sensitive target organ for other environmental stressors.…”
Section: Effects On Organ Weightsmentioning
confidence: 86%
“…According to the Environmental Protection Agency (EPA), TNT affects human, aquatic, and terrestrial life forms and lists it as a class C potential human carcinogen (Smets et al 2007). TNT metabolites induce reproductive toxicity through oxidative DNA damage as shown by animal models and epidemiological studies (Homma-Takeda et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Possible application areas are not only restricted to bioremediation (Hannink et al 2001), but also to specific biocatalysis (Kadiyala et al 2003) and cancer therapy (Denny 2002;Knox et al 2003). Through their activity, they decisively determine the toxicity of nitroaromatic compounds (Homma-Takeda et al 2002;Padda et al 2003), although their physiological relevance is still largely unknown. Nitroreductases may be classified into two types.…”
Section: Enzymes Involved In Tnt Transformationmentioning
confidence: 99%